Peculiarities of the course of the early postoperative period in patients after correction of left ventricular aneurysm with concomitant ischemic mitral insufficiency - S. Rudenko; В. В. Lazoryshynetz; O. Trembovetskaya; A. Rudenko; O. Gogaeva (Ukrainian Journal of Cardiovascular Surgery, 2018)
Ischemic heart disease (ІHD) is a leading place among the topical medical and social problems. Myocardial infarction (МІ) is the most formidable complication of ІHD. Many of these patients, after discharge from the hospital, still had significant violations of the function of the left ventricle (LV). One of the terrible complications of MI is the inadequacy of mitral valve ischemic genesis. This pathology occurs in almost 20–25% of cases after acute myocardial infarction (AMI) and more than 50% of patients who have symptoms of congestive heart failure after AMI. The presence of mitral regurgitation in ІHD negatively affects the survival of patients. Mortality during the first year is from 40 to 70%. At the National Institute of Cardiovascular Surgery operated 693 patients with a left ventricular aneurysm. The patients were divided into two groups – the presence or absence of mitral insufficiency of the ischemic genesis at the preoperative stage. The first group included 259 (37.4%) patients with mitral insufficiency, and the second group – 434 (62.6%) without concomitant mitral insufficiency. Groups of patients were equivalent to demographic indicators and the frequency of the detection of concomitant pathology of the nervous and vascular systems of the body. Most of the patients under study group 1 related to NYHA class 3–4 (71.8%), while in the second group, more than a third of patients (39.2%) were in the NYHA class 1–2 functional class. The intraoperative data of the artificial blood circulation of the two groups did not different. In the postoperative period, in the group with preoperative mitral insufficiency, the time of mechanical ventilation is almost twice as high (11.6±36.4 h and 6.5±13.9 h) (p=0.01). Acute heart failure II and more degrees occurred in 1.5 times more often in group №1 (p=0.02). Acute cerebrovascular accidents in the second group are diagnosed in 2.5% of patients, and in group 1 – in 5,0% of patients (p>0,05). The mortality in group 1 increases four times the death rate in group 2 (3.9% and 0.9%, respectively) (p=0.01). The presence of preoperative mitral insufficiency, even if it does not require correction, significantly worsens the course of the early postoperative period of patients after surgical correction of the left ventricular aneurysm and leads to an increase in the incidence of postoperative complications and significantly increases mortality.